Cross-border Activity of Japanese Banks - Lam, Waikei (IMF Working Papers; Working Paper, 2013)
This paper explores the determinants of Japanese banks' overseas expansion and assesses whether the growing cross-border activity will continue under the new macroeconomic policies referred as 'Abenomics'. The analysis finds that Japanese banks are well positioned to scale up foreign exposures, thanks to their relative resilient balance sheets and continued growth in the region. Stronger domestic growth in Japan could mitigate the pace, but is unlikely to reverse the expansion as global and regional pull-factors play a more prominent role in the growth of cross-border claims. Increasing cross-border activity could pose funding risks and supervisory challenges and require continued close monitoring.